Community-Based Health Screening: Assessment of Oxygen Saturation (SpO2), Heart Rate, and Body Temperature in RT 005 RW IV, Kelurahan Gondoriyo, Ngaliyan, Semarang - Affa Ardhi Saputri; Susilawati; Hartono; Istikomah; Yeni Rossa Damayanti; Milta Bima Say Putri (Community Research and Application Journal (CRAJ), 2026)
Vital signs, namely oxygen saturation (SpO₂), heart rate (HR), and body temperature, are fundamental physiological indicators of overall health status. Their periodic monitoring in the general population supports early identification of oxygenation disorders, cardiovascular conditions, and infection or inflammation before these progress to more serious conditions. This research-based community service activity carried out a free vital-sign screening for residents of RT 005 RW IV, Kelurahan Gondoriyo, Ngaliyan, Semarang, on 28 June 2026, using a pulse oximeter for SpO₂ and HR and a non-contact infrared thermometer for body temperature. Twenty community members were screened, with duplicate SpO₂ and HR measurements taken for each participant; the second reading of each was used as the analysis reference after the first-attempt readings were assessed as reflecting an initial probe signal-stabilization phase. Results showed a mean SpO₂ of 96.8% (range 79–100%), with 90% (18 of 20 participants) within the normal range (≥95%) and one participant showing severe hypoxemia (79%) requiring urgent referral. Mean HR was 59.2 beats per minute (range 35–100), with only 35% (7 of 20) within the standard resting range of 60–100 bpm; two participants showed severe bradycardia (35 and 37 bpm) requiring immediate electrocardiographic evaluation. Mean body temperature was 35.65°C (range 34.5–36.3°C), a pattern consistent with the known sensitivity of non-contact infrared thermometry to outdoor ambient conditions. The activity produced individualized referral recommendations for participants with critical findings and supports periodic, six-monthly community vital-sign screening, particularly for residents above 40 years of age.